COMBINATION BENSON RELAXATION AND MURROTAL ALQURAN TO DECREASE ANXIETY, STRESS, AND DEPRESSION HEMODIALYSIS PATIENTS: AN EXPERIMENTAL STUDY - Rohmawati, Riska; Sari, Ratna Yunita; Faizah, Imamatul; Hasina, Siti Nur (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Anxiety, stress and depression in hemodialysis patients often occur due to changes in lifestyle and boredom undergoing therapy. Data from the hospital 63.9% of hemodialysis clients experienced anxiety, 51.7% experienced stress, and 60.5% experienced depression. Objectives: The purpose of this study was to determine the effect of the combination of Benson relaxation and Murrotal Al-Quran in hemodialysis patients at Islamic hospital. Methods: The design of the research was quasi-experiment with pre-posttest control group design. The sample of the research was 180 respondents that divided into three groups: 60 respondents in intervention group with combination of Benson relaxation and Murrotal Al-Quran, 60 respondents in intervention group with Benson relaxation, and 60 respondents in control group (no intervention). The intervention groups were given combination of Benson relaxation and Murrotal Al-Quran for 15 minutes once daily for 1 month. Research instruments using DASS (Depression Anxiety Stress Scale) to measure the anxiety, stress, and depression. Results: The t-test analysis found that the decrease in anxiety, stress, and depression was more common in the Benson relaxation and Murrotal Al-Quran combination group. While the Manova test showed that there were differences in the intervention group and the control group with the strength of differences in anxiety (68.7%), stress (68.4%), and depression (58.2%). Conclusion: Benson relaxation combination therapy with Murrotal Al-Quran is more effective in reducing anxiety, stress, and depression levels in hemodialysis patients. Nurses can implement this intervention in order to meet the patients’ psychological needs.